7 - L’Afrique peut-elle peser dans le débat international sur la migration ? Pistes autour de la teraanga ou de l’hospitalité - Seck, Abdourahmane (African Sociological Review, 2023)
This paper highlights some of the reasons, imaginaries and practices that may help Africa build a voice which matters in the international debate on migration. The article develops a critical and decolonial reflection based on observations and conversations mainly engaged in Saint- Louis, Senegal, with white European migrant communities. This reflection also calls upon other situations embedded in current events and in the author’s own migration experience. Based on this approach and these materials, the idea of hospitality (teraanga) is revisited thanks to lessons learned from Africa.